The hive queen - Sutherland, Tui, 1978- (New York : Scholastic Press, 2019)
Growing up in the hives, Cricket has always had a million questions. Why are trees forbidden, even in art? Why do her parents seem to hate her? And the biggest, most dangerous and secret question of all: why is Cricket immune to Queen Wasp's powers? Whenever the queen takes control of all the HiveWings, speaking through their mouths and seeing through their eyes, Cricket has to hide, terrified of being discovered. Now she's hiding again, wanted for stealing the Book of Clearsight along with her new SilkWing friends, Blue and Swordtail, and the fierce LeafWing, Sundew. The fugitives need answers, and fast, in order to prevent a LeafWing attack. But Cricket has more questions than ever. How can she stay hidden and discover the queen's deadliest secret? And if she does succeed--can a powerless dragonet really do anything to topple a regime and stop a war?
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Good and evil -- Juvenile fiction; Adventure stories; Fantasy fiction